Principles for the Design of Online A/B Metrics - Machmouchi, Widad; Buscher, Georg (SIGIR '16: Proceedings of the 39th International ACM SIGIR conference on Research and Development in Information Retrieval, 2016)
In this paper, we describe principles for designing metrics in the context of A/B experiments. We share some issues that comes up in designing such experiments and provide solutions to avoid such pitfalls.